The LTAR Integrated Common Experiment at Southern Plains - Fortuna, Ann‐Marie; Northup, Brian; Starks, Patrick J.; Moriasi, Daniel N.; Steiner, Jean L.; Wagle, Pradeep; Zhang, Xunchang (John); Flanagan, Paul; Busteed, Phillip; Teet, Stephen; Witt, Travis W.; Hunt, Sherry; et al. (Journal of environmental quality, 2024)
The Southern Plains (SP) is one of 18 Long‐Term Agroecosystem Research network sites that combine strategic research projects with common measurements across multiple agroecosystems. Projects at the SP site focus on the use of indicator measurements to aid in assessment of land and nutrient management's impact on soil health, water quality, carbon and water balances, and forage biomass‐quality in diversified, adaptive crop‐livestock systems designed to overcome shifts in natural resources and climate. The prevailing treatment is tilled winter wheat (Triticum aestivum L.) that is grazed, hayed, harvested for grain, or grazed and harvested for grain. The alternative treatment is year‐round annual cover crop forage mixes for cattle (Bos taurus) production planted in fall and spring under conservation tillage management. The area is subject to variable weather and climatic shifts that reduce the potential to diversify forage crops and limit grazing in southern tall grass prairies and small grain systems. Incorporation of fertilized, rain‐fed, annual cool and warm season mixtures of cover crops could fill forage gaps. The presence of year‐round ground cover reduces sediment and nutrient loading to surface waters while enhancing soil health and water holding capacity. Tools to aid agricultural producers and land and water resource managers have been developed and implemented to determine how climate, topography, and varying conservation management practices alter hydrological structures, greenhouse gas emissions, water usage, and soil resources. Core Ideas The southern Plains has diverse geography, climate, land types, soils, and agroecosystems. Cool and warm season annual mixes in the alternative treatment serve as year‐round cover and fill a forage gap. Annual cool and warm season forage mixes in conservation tillage obtain adequate moisture despite climatic extremes. Models and data collection at varying scales aid in determining when alternative management is appropriate. Plain Language Summary The wheat pasture ecoregion of the southern Great Plains (SGP) is subject to highly variable weather and changing climate that threaten rainfed diverse agricultural systems leading to droughts with intermittent flooding. The SGP is one of 18 Long‐Term Agroecosystem Research (LTAR) sites that support internally and externally federal and state funded projects across crop, range, and pasture lands. Scientists at the SGP LTAR site near El Reno, Oklahoma at the Central Plains Agricultural Research Center are developing and implementing dynamic, sustainable crop and forage‐based beef production systems that perform in a highly variable climate. Researchers assist agriculture producers and land and water resource managers by developing and implementing tools to determine the effects of climate, topography, and varying conservation managements on plant productivity, soil health, natural resources, greenhouse gas emissions, water quantity and quality, and hydrological structures.